2018
DOI: 10.5713/ajas.17.0903
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and antioxidant capacity of some tropical edible plants

Abstract: ObjectiveTo find biological functions such as antibacterial and antioxidant activities in several tropical plants and to investigate the possibility of antibiotic substitute agents to prevent and treat diseases caused by pathogenic bacteria.MethodsPlants such as Poncirus trifoliata fruit (Makrut), Zingiber officinale Rosc (Khing), Areca catechu L. (Mak), Solanum melongena L. I (Makkhuayao), and Solanum melongena L. II (Makhurapro) were extracted by methanol, n-hexane, chloroform, ethyl acetate, butanol and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several studies [42,66,67] have been performed with the aim of studying the antioxidant potential (through in vitro tests) of different parts of eggplant and positive and promising results were observed.…”
Section: Antioxidant Antimicrobial Cytotoxic and Hepatotoxic Activity Of The Hydroethanolic Extract Obtained From The S Melongena Fruit Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies [42,66,67] have been performed with the aim of studying the antioxidant potential (through in vitro tests) of different parts of eggplant and positive and promising results were observed.…”
Section: Antioxidant Antimicrobial Cytotoxic and Hepatotoxic Activity Of The Hydroethanolic Extract Obtained From The S Melongena Fruit Bmentioning
confidence: 99%
“…Other authors [10,67] studied the antimicrobial action of S. melongena (fruits and/or leaves) and the results evidenced antibacterial and antifungal potential.…”
Section: Antioxidant Antimicrobial Cytotoxic and Hepatotoxic Activity Of The Hydroethanolic Extract Obtained From The S Melongena Fruit Bmentioning
confidence: 99%
“…Soberón et al [68] declared that methanolic and the aqueous extract of Ligaria cuneifolia and Jodina rhombifolia leaf have the MICs ranging from 2.5 to 156 µg/mL and 5 mg/mL, respectively, against Xcc, while these extracts were bacteriostatic. Hong et al [69] found that phytochemicals extracted from Zingiber officinale rose have the MIC equal to 1.94 mg/mL against Pantoea agglomerans. In agreement with these data, the saturated and unsaturated fatty acids as major constituents of AWME from the H. illuscens larvae fat, possess the high antimicrobial effect against five important plant bacteria pathogens having MIC = 0.78 mg/mL, MBC = 0.78-1.56 mg/mL, and IC 50 = 366.8 ± 0.38-485.4 ± 0.4 mg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Gallardo et al [ 44 ] evaluated the effect of supplementing linseed oil (3%) and natural or synthetic vitamin E in lactating Churra ewes with their lambs and observed that oil supplementation did not affect ADG, BW or LWW of suckling lambs. Under tropical and subtropical conditions, perhaps the best feeding strategy is to use extracts and byproducts from native plants [ 45 ]. In this context, even though the use of oils was reported to increase dietary energy density and improve lamb performance [ 44 ], the use of plant extracts may be an appropriate choice as they are available and easy to mix into diets.…”
Section: Discussionmentioning
confidence: 99%